2016
DOI: 10.1093/jnen/nlw025
|View full text |Cite
|
Sign up to set email alerts
|

Human Traumatic Brain Injury Results in Oligodendrocyte Death and Increases the Number of Oligodendrocyte Progenitor Cells

Abstract: Oligodendrocyte (OL) death may contribute to white matter pathology, a common cause of network dysfunction and persistent cognitive problems in patients with traumatic brain injury (TBI). Oligodendrocyte progenitor cells (OPCs) persist throughout the adult CNS and may replace dead OLs. OL death and OPCs were analyzed by immunohistochemistry of human brain tissue samples, surgically removed due to life-threatening contusions and/or focal brain swelling at 60.6 ± 75 hours (range 4-192 hours) postinjury in 10 sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 97 publications
1
37
0
Order By: Relevance
“…Oligodendrocyte lineage progenitors (OPCs) are in close apposition with pericytes in the perivascular space, with evidence for mutual interactions, promoting proliferation . Surgical TBI resections have shown an increase in OPC number at injury site and transient proliferation of OPC noted between 7 to 21 dpi in a diffuse TBI model . In our study significant proliferation was confirmed, with Olig2/MCM2 + cells peaking at 13 dpi then falling to control levels in chronic lesions.…”
Section: Discussionsupporting
confidence: 60%
“…Oligodendrocyte lineage progenitors (OPCs) are in close apposition with pericytes in the perivascular space, with evidence for mutual interactions, promoting proliferation . Surgical TBI resections have shown an increase in OPC number at injury site and transient proliferation of OPC noted between 7 to 21 dpi in a diffuse TBI model . In our study significant proliferation was confirmed, with Olig2/MCM2 + cells peaking at 13 dpi then falling to control levels in chronic lesions.…”
Section: Discussionsupporting
confidence: 60%
“…Nonetheless, our results do indicate that pediatric mTBI not only dysregulates OL lineage cell formation but will ultimately lead to increased levels of mature OLs, especially when the injury is repeated. Adult TBI has been shown to lead to apoptosis of existing OLs followed by remyelination [78-80]. However, considering the incomplete myelination in AC at the time of TBI [81] and the fact that many OLs are undergoing development at this age [24-26], it is likely that the OL lineage cell development and maturation itself are altered, leading to abnormal WM development.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, other techniques to better detect Olig2+ cell loss should be used, such as a different oligodendrocyte marker (e.g., CC1) and/or markers for apoptosis (e.g., caspase-3, TUNEL). Oligodendrocyte death following TBI is a known phenomenon, observed early following injury, between 12 h and 7 d for fluid percussion models [68,69], and in human studies [70]. Oligodendrocytes are vulnerable cells, sensitive to excitotoxicity (secondary to glutamate and other excitatory neurotransmitters release in DAI) and to oxidative stress (as, to sustain myelination process, they have high metabolic rates and consume high levels of ATP, but only have scarce concentration of glutathione), as well as to inflammatory cytokines, all conditions present in TBI [39,71].…”
Section: Oligodendrocyte Lossmentioning
confidence: 99%
“…However, it also stains pericytes, thus making it necessary to co-label it with Occludin, a tight-junction protein, to confidently distinguish the two NG2+ cells. While NG2 is commonly used as marker of OPCs, it is also expressed by glial cells differentiating into neurons or astrocytes, as well as macrophages [40,70,[89][90][91][92]. For this reason, the analysis of NG2 immunostaining was only qualitative, supported by cell morphology observed at high magnification, while quantitative OPC analysis was based on PDGFRa mRNA.…”
Section: Tbi-induced Opcs Reactionmentioning
confidence: 99%